School Administration Towards Becoming an Innovative School - Pongsura, Kitisuk; Meechai, Chaloemphon; Prasongsang, Chaiwat (Rajapark Journal, 2025)
This academic article proposes the management of educational institutions towards becoming innovative schools. Current educational management focuses on coordinating and managing internally and externally to create an effective learning environment. Administrators, teachers, and staff must work together to achieve quality educational goals. However, developing schools into "innovative schools" is essential in an era where technology and society are rapidly changing. This involves applying new ideas, technologies, and effective management methods in teaching and administration. The transition to innovative schools requires curriculum improvements that link to the skills necessary for the 21st century, the use of digital technology in learning, building community partnerships, and promoting the development of essential skills for students, such as analytical thinking and problem-solving. Creating a learning culture that supports creativity will enable schools to prepare students for the future effectively. The processes involved in managing educational institutions to transform into innovative schools include key principles of management: 1) creating a vision and commitment to sustainable development; 2) applying digital technology in the teaching process; 3) developing teachers and staff for lifelong learning; 4) fostering a culture of learning that emphasizes creativity and problem-solving; and 5) community involvement and linking with various sectors. Effective management of educational institutions will enable schools to become innovative and capable of producing students with knowledge, skills, and desirable characteristics ready to face various challenges in a rapidly changing world.